Geochemistry and Sr–Nd isotopes of the Late Mesozoic lamprophyres in the Chaohu area, eastern China: Petrogenesis and tectonic implications. (24th January 2022) - Chen, Mo; Li, Longming; Kan, Tianxiang; Liu, Hang; Zhao, Xilin; Li, Jiahao; Han, Xu
Abstract: Late Mesozoic lamprophyres are widespread in the Chaohu area of the Lower Yangtze region, eastern China. These mantle‐derived rocks are of great significance for understanding the characteristics of mantle source and tectonic environment of eastern China during the Late Mesozoic. The lamprophyres from the Chaohu area can be divided into two types. The type‐I lamprophyres have low SiO2 (43.8–44.5 wt.%) and TiO2 (1.06–1.14 wt.%), high MgO (13.5–17.5 wt.%) and high contents of compatible elements, and are enriched in LREE and LILE but depleted in HFSE. They have high initial 87 Sr/ 86 Sr (0.70767–0.70904) and negative εNd ( t ) (−4.8 to −4.4). The type‐II lamprophyres are characterized by low contents of SiO2 (43.0–45.4 wt.%), high TiO2 (1.74–2.55 wt.%), MgO (9.17–15.4 wt.%), and compatible elements. They are also enriched in LREE and LILE but depleted in HFSE. They show enriched Sr‐Nd isotopic compositions with initial 87 Sr/ 86 Sr values (0.70773–0.70886) and εNd ( t ) values (−8.6 to −7.8). The type‐I lamprophyres show higher Mg # and MgO contents but significant lower TiO2 than the type‐II lamprophyres. In addition, the type‐I lamprophyres have relatively similar initial 87 Sr/ 86 Sr ratios but higher εNd( t ) values than the type‐II lamprophyres. The difference of geochemical characteristics between the type‐I and type‐II lamprophyres may be caused by different degrees of partial melting of an amphibole‐bearing garnet lherzolite mantle. The lithospheric mantle was metasomatised by the fluids caused by the rollback of the Paleo‐Pacific plate subduction during the Late Cretaceous.